Pengaruh Harga Emas dan Nilai Tukar Rupiah Terhadap Indeks Harga Saham Gabungan Yang Terdapat di Bursa Efek Indonesia Periode 2006-2017 - Arni Hardiyanti (Universitas Batanghari Jambi, 2019)
The purpose of this research conducted to analyze The Effect Of Gold Prices And The Rupiah Exchange Rate On The Composite Stock Price Index Found On the Indonesia Stock Exchange for the period 2006-2017. Objective of the research to all companies in the joint stock price index.Technique analytical use description quantitative analysis method, which is using analysis multiple linear regression analysis doing classical assumption test that normality test, multicolinearity test, heteroscedasticity test, autocorrelation test and hypothesis test is F test, T test and coefficient of determination test which aim to find out whether the conclusions in the sample can be applied to the population can be generalized or not.The result of this research indicate about Effect Of Gold Prices And The Rupiah Exchange Rate On The Composite Stock Price Index Found On the Indonesia Stock Exchange for the period 2006-2017. Simultaneously with the number of Fcount 11,833 and Ftable 4,26 , it can be seen Fcount > Ftable is 6,085 > 4,26 , meaning there is a significant Effect Of Gold Prices And Rupiah Exchange Rate.The partial influence about Effect Of Gold Prices And The Rupiah Exchange Rate On The Composite Stock Price Index Found On the Indonesia Stock Exchange for the period 2006-2017 with the number of gold prices Tcount 1,773 and Ttable 2,26216 is the meaning Tcount < Ttable , 1,773 < 2,26216 ,the number of rupiah exchange rate tcount 2,057 and ttable 2,26216 is the meaning tcount < ttable , 2,067 < 2,26216 , meaning that the price of gold does not have a positive effect on the composite stock price index period 2006-2017.